Internal climate variability and projected future regional steric and dynamic sea level rise - Aixue Hu (Nature Portfolio, 2018)
As the global climate becomes warmer, the associated rising sea level could pose significant threats to island and coastal communities. Here the authors show that internal climate variability plays a key role in determining this sea level rise, especially in the next few decades.